Janus-Faced Grounding - Christopher Fruge (Ergo, An Open Access Journal of Philosophy)
A common view in the metaphysics of ground is that all grounding facts are grounded. This generates an infinite regress of ever more grounding of grounding facts, but most grounding theorists take the regress to be harmless. However, in this paper, I argue that the regress is in fact vicious, therefore some grounding facts are ungrounded. Since the regress appears to fall out of two plausible principles of fundamentality, I offer a new interpretation of them that allows for ungrounded grounding facts.